Chapter 11 Higher education students as consumers? Evidence from England - Brooks, Rachel (Taylor & Francis, 2020)
In this chapter, we draw on an analysis of English policy documents and focus groups with students at three English higher education institutions, to explore some of the complexity in the ways in which the concept of student-as-consumer is discussed by both those formulating policy and the intended recipients. In relation to policies, this is evident in some of the apparent contradictions within government documents which, on one hand, emphasise strongly many aspects of a consumer discourse (foregrounding ideas around investment, choice and ensuring value of money) but, on the other hand, also discuss in some detail the vulnerability of students and their need of protection- which is clearly at odds with the notion of an 'empowered consumer'. With respect to students, a similar degree of complexity can be seen in their differential awareness of the student-as-consumer discourse, and their varied responses to it.